Service Quality and Brand Image on Saving Intention in Syariah Banks in Indonesia, Moderated by Religiosity - Suheri, Tommy; Saufi, Akhmad; Supryadi, Didy Ika (Universitas KH. Abdul Chalim Mojokerto, 2026)
The Islamic banking industry in Indonesia has experienced steady institutional development, yet its market share remains relatively low, indicating stagnant public interest, particularly in savings products. This study investigates the influence of Service Quality and Brand Image on Saving Intention in Islamic banks, with Religiosity serving as a moderating variable. Using a quantitative associative approach, data were collected from 170 respondents across different regions of Indonesia through an online questionnaire measured with a five-point Likert scale. The analysis was conducted using Partial Least Square (PLS) with SmartPLS software. The findings show that both Service Quality and Brand Image significantly and positively influence Saving Intention, with Brand Image identified as the most dominant factor. Religiosity functions as a pure moderator, strengthening the relationship between Service Quality and Saving Intention as well as between Brand Image and Saving Intention, although it does not directly affect Saving Intention. The model demonstrates strong explanatory power, reflected in an R-square value of 0.912, indicating that 91.2% of the variance in Saving Intention is explained by the examined variables. These results suggest that saving behavior in Islamic banking is shaped not only by rational and functional factors but also by emotional and spiritual considerations. Therefore, Islamic banks should focus on improving service quality, strengthening brand image, and consistently embodying Islamic values ​​to enhance customer loyalty and increase saving intention, while contributing to more effective customer-oriented strategies in the Islamic banking sector.